Pengaruh Media Youtube Terhadap Pengetahuan dan Sikap Siswa Tentang Kesehatan Reproduksi Remaja di SMK Kristen Makale - Sutrisno Papayungan; Yuvita Setiana; Hansen Lemana; Martini Lilisantosa; Yanti Tandirongang (Indonesian Journal of Science and Public Health, 2024)
Sexuality problems such as premarital sex in adolescents, risky sex, and abortion in adolescence occur due to the low knowledge of adolescents about reproductive health. The existence of adolescent reproductive health education with the selection of effective methods is expected to increase knowledge about reproductive health. Research Objective: To determine the effect of providing education through YouTube media on the level of knowledge and attitude of adolescents about adolescent reproductive health at SMK Kristen Makale. Research Methods: This research is a pre-experimental study using pre test and post test one group design which was conducted in June - July 2023. The sample of this study was as many as SMK Kristan Makale students who were randomly selected with a total sample of 50 people. Data analysis using. SPSS application with Kolmogorov-Smirnov statistical method. The measuring instruments used were .pretest and.post test. Research Results: There is an increase in students' knowledge and attitude about Reproductive Health after receiving educational intervention through Youtube.